2004
DOI: 10.1038/labinvest.3700166
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor-associated expression of keratinocyte growth factor and its possible role in the inhibition of apoptosis in human breast cancer

Abstract: Although estrogen is known to play a crucial role in the pathogenesis of breast cancer, the molecular mechanisms underlying the action of estrogen remain elusive. In the present study, we focused on keratinocyte growth factor (KGF) and its receptor (KGFR) in the pathogenesis of breast cancer, as a growth factor mediating estrogen action, since significant roles of KGF were demonstrated in various steroid hormone-dependent tissues. First, using paraffin-embedded specimens from 42 breast cancer patients, we exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
44
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 45 publications
(64 reference statements)
10
44
0
Order By: Relevance
“…It has been reported that FGFR2 is involved in estrogen-related breast carcinogenesis (Zhang et al 1998;Tamaru et al 2004), and is more likely to be overexpressed in ER + than in ER -breast cancer (Tozlu et al 2006). Consistent with these studies, Garcia-Closas et al (2008) found that there was an association between rs2981582C/T and both ER + and ER -breast cancer.…”
Section: Discussionsupporting
confidence: 76%
“…It has been reported that FGFR2 is involved in estrogen-related breast carcinogenesis (Zhang et al 1998;Tamaru et al 2004), and is more likely to be overexpressed in ER + than in ER -breast cancer (Tozlu et al 2006). Consistent with these studies, Garcia-Closas et al (2008) found that there was an association between rs2981582C/T and both ER + and ER -breast cancer.…”
Section: Discussionsupporting
confidence: 76%
“…In particular, the perallele odds ratio was higher for ER-positive rather than for ER-negative BC (Ahmed et al, 2009). This finding is consistent with the involvement of FGFR2 in estrogenrelated breast carcinogenesis (Tamaru et al, 2004), and with higher levels of FGFR2 expression in ER þ than ERÀ cell lines and tumors (Zhang et al, 1999). Stacey et al genotyped B300 000 SNPs in 1600 Icelandic individuals with BC and 11 563 controls.…”
Section: Fgfr2supporting
confidence: 63%
“…There is a common expectation that apoptosis is deficient in cancer. In fact, this is generally not the case: apoptosis is normal or actually enhanced [36][37][38][39]. However, the fractal dimensionality of the mitotic compartment is increased to a greater extent than that of the apoptotic compartment.…”
mentioning
confidence: 99%